Optimization of Maritime Security Through National Shipyard Redistribution: A Case Study in Indonesia: Optimalisasi Keamanan Maritim Melalui Redistribusi Galangan Kapal Nasional: Sebuah Studi Kasus di Indonesia - Riyanto, Slamet; Prasetya , Wirawan Ady; Darmawan, Budi (Indonesian Journal of Innovation Studies, 2023)
This study investigates the strategic optimization of Indonesia's National Shipyard Industry, focusing on its role in enhancing maritime security in the Indonesian Archipelago II (ALKI II) region. Utilizing a TOWS analysis and drawing on expert opinions in maritime security, the research examines the internal and external factors influencing the industry, as well as potential future threats. The relocation of the National Capital to Penajem Pasir Utara, East Kalimantan, emerged as a pivotal factor, offering a geographically centralized location and favorable environmental conditions, and presenting an opportunity to equalize the development of the Galkapnas Industry. The results indicate that almost 60% of Galkapnas are concentrated in Java and Batam, highlighting the need for aggressive strategic action to redistribute the industry and facilitate maintenance functions in ALKI II. The study underscores the importance of coordinated efforts among various ministries, particularly the Ministry of Defense, in achieving this redistribution, and concludes with recommendations for stakeholders to embrace the challenge of building and optimizing Galkapnas through extensive development in the ALKI II region, thereby enhancing the Navy's operational capabilities.Highlights: The concentration of almost 60% of Galkapnas in Java and Batam necessitates aggressive redistribution for optimizing maritime security. Relocation of the National Capital to Penajem Pasir Utara presents strategic opportunities for balanced development and industrial growth in the maritime sector. Coordination among ministries and stakeholders is crucial for implementing the recommended changes, enhancing the Indonesian Navy's operational capabilities. Keywords: Maritime Security, National Shipyard Industry, Indonesia, TOWS Analysis, Galkapnas Redistribution